Ethnotheological Studies on the Substance of Folk Religion as Local Theology among the Dani Ethnic Group in Baliem Village, Papua: Towards a Contextual Ministry - Mawikere, Marde Christian Stenly; Hura, Sudiria; Mawikere, Jean Calvin Riedel; Mawikere, Daniella Beauty Melanesia (LIMMUD: Jurnal Ilmu Keagamaan dan Sosial Humaniora, 2024)
This study investigates the interplay between the folk religion of the Dani people in Baliem Village, Papua, and its potential to inform a local theology that supports contextual ministry. By applying an ethnotheological framework, the research examines how Dani cultural and religious beliefs—particularly those enshrined in the Nabelan-Kabelan and Naruekul mythologies—can serve as a foundation for contextual evangelism. Through qualitative methods, including ethnographic fieldwork and content analysis of relevant literature, this study identifies key elements of Dani folk religion that either hinder or facilitate the integration of Christian teachings within Dani society. The findings highlight the intricate relationship between indigenous spirituality and Christian ethics, suggesting that a contextualised approach to ministry is crucial for effective evangelism among the Dani people. The paper concludes by offering recommendations for the development of contextual ministry strategies that engage with the Dani’s cultural and theological worldview.